(untitled) (Journal of Pharma Insights and Research, 2025)
Alkanna tinctoria (L.) Tausch, is a Mediterranean herb that belongs to Boraginaceae family. It is a valuable medicinal plant with various pharmacological properties. The roots of A. tinctoria contain bioactive naphthoquinones, primarily alkannin and shikonin, along with their derivatives, which exhibit notable antimicrobial, anti-inflammatory, and wound-healing activities. Modern research has shown many traditional applications while discovering new therapeutic potentials, particularly in cancer treatment and diabetic wound management. The plant’s rich phytochemical profile includes terpenoids, flavonoids, and phenolic compounds that contribute to its antioxidant and anti-inflammatory properties. Recent innovations in drug delivery systems, such as chitosan-based nanoparticles and electrospun nanofibers, have enhanced the efficacy of A. tinctoria extracts in wound healing applications. The plant also shows promise in cosmeceuticals due to its UV-protective and anti-aging properties. Despite these benefits, safety concerns exist regarding trace amounts of pyrrolizidine alkaloids, necessitating careful consideration in systemic applications. Advanced analytical techniques have enabled detailed characterization of bioactive compounds and their mechanisms of action. The usage of A. tinctoria in modern therapeutic applications represents a successful bridge between traditional medicine and contemporary pharmaceutical research, though additional clinical studies are needed to fully establish its therapeutic efficacy